Experimental study of post-CHF heat transfer in a vertical tubular test section. (February 2021) - Liu, Qingqing; Sun, Hanxing; Liu, Yang; Kelly, Joseph; Sun, Xiaodong
Highlights: Formation and collapse of dry patches in post-CHF regime are studied experimentally. Dry temperature and quench temperature are analyzed. Convective heat transfer coefficients are compared with existing correlations. Abstract: In this paper, post-CHF (critical heat flux) experiments are performed in a vertical tubular test section with water as the working fluid to study the heat transfer characteristics during the process of formation, growth, and propagation of dry patches. The formation, growth, and propagation of the dry patches are indicated from the measured wall temperatures of the test section. The so-called dry temperature and quench temperature, corresponding to the formation and departure of dry patches, are obtained by analyzing the first-order derivative of the measured wall temperatures. The temperature gradient along the axial direction of the test section wall is also calculated, up to 15 °C/mm. Large temperature gradients result in axial heat conduction as well as thermal stresses in the test section. The convective heat transfer coefficient for the dry patches is calculated based on the saturation temperature of the fluid and compared with three heat transfer correlations in the literature. The computed convective heat transfer coefficient for the dry patches in our experiments is larger than the calculated results of the correlations, especially for conditions of relatively low wall superheats.